Molecular and physiological responses of recalcitrant indica rice to lignosulfonates during callus regeneration - Low, Lee Yoon (2018)
Lignosulfonate (LS) is commonly used as an enhancer to promote plant growth. The recalcitrant Oryza sativa indica cv. MR219 rice is an important local high yield rice cultivar that is widely cultivated in Malaysia. However, low callus regeneration rate of MR219 hinders further exploitation in cultivar improvement. Hence, LS was introduced in the culture medium in effort to enhance in vitro cultivation of MR219. To date, the effects of LS on regeneration of MR219 has not been reported. Therefore, this study was undertaken to evaluate the effects of LS on callus proliferation, shoot induction and shoot growth of MR219. The MR219 calli were proliferated on MS supplemented with different types (aNaLS and aCaLS) and concentrations (50, 100, 150, 200 mg/L) of LS. The optimum callus proliferation rate (88%) was obtained in week 3 on MS supplemented with 100 mg/L aCaLS in the presence of plant hormone. However, both LSs did not enhance the shoot induction efficiency whereby 50% of the shoot induced was albino in MS fortified with 100 mg/L CaLS. In shoot growth study, shoot apices were cultured in MS supplemented with different types (aNaLS and aCaLS) and concentrations (100, 200, 300 and 400 mg/L) of LS. The optimum shoot growth was observed in MS supplemented with 300 mg/L aNaLS that is taller by 26% of control height. To understand the growth promoting effects of LS, aCaLS treated callus was used as a study model. Results showed that aCaLS increased callus proliferation rate by 67% and adventitious root formation by 62% in MS without hormone. Hence, it was shown that the LS effect was found to be independent of hormone. Under scanning electron microscopy, adventitious roots were seen protruding out from aCaLS-treated calli. Further expression analysis of adventitious root-related genes (OsWOX11, OsAUX1 and OsIAA23) on treated calli, OsWOX11 expression recorded 1.7-fold expression increment, implying a positive role of aCaLS in adventitious root development. In addition, aCaLS-treated calli recorded 1.2-fold higher endogenous indole-3-acetic acid (IAA) content and increment of nutrient ions (Na, K, Ca, Mg, Fe, Mn, Zn and Cu) uptake. Consistently, expression analysis of auxin-related genes (OsASA1, OsTAA1 and OsYUC1) and nutrient uptake-related genes (OsAKT1, OsHAK5, OsCBL, OsCIPK23 and OsCamk1) also showed a similar increment trend. The Ca increment was observed throughout four weeks but the major increment of K was only detected starting from week two. The observed rise of Ca following the enhancement of endogenous K content suggested the possible cross-talk between these ions uptake. The LC-MS/MS analysis suggested that there was an increased in carbon and nitrogen metabolisms in aCaLS treated callus. Taken together, the presence of aCaLS improved MR219 callus proliferation, up-regulated endogenous auxin synthesis, nutrients uptake and carbon-nitrogen metabolisms that ultimately contributed to calli growth enhancement. The findings of this study would be useful on improving the in vitro cultivation of the recalcitrant rice cultivars.